2014
DOI: 10.1128/jcm.02220-13
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biofilms on Needleless Connectors for Central Venous Catheters: Comparison of Standard and Silver-Coated Devices Collected from Patients in an Acute Care Hospital

Abstract: e Microorganisms may colonize needleless connectors (NCs) on intravascular catheters, forming biofilms and predisposing patients to catheter-associated infection (CAI). Standard and silver-coated NCs were collected from catheterized intensive care unit patients to characterize biofilm formation using culture-dependent and culture-independent methods and to investigate the associations between NC usage and biofilm characteristics. Viable microorganisms were detected by plate counts from 46% of standard NCs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
0
26
1
2
Order By: Relevance
“…However, all these clusters revealed a strong negative correlation with Bacillus , Sphingobium , Hydrogenophaga , Thauera , Thermomonas , and Gemmobacter . It is important to note that most of these bacterial genera are known players in biofilms formation, including synergic multi-genera biofilms, on various hospital dry surfaces [36,37]. Biofilms matrix is a resistance mechanism that could stabilize a bacteria community in a selective environment such as (N)ICUs [38].…”
Section: Resultsmentioning
confidence: 99%
“…However, all these clusters revealed a strong negative correlation with Bacillus , Sphingobium , Hydrogenophaga , Thauera , Thermomonas , and Gemmobacter . It is important to note that most of these bacterial genera are known players in biofilms formation, including synergic multi-genera biofilms, on various hospital dry surfaces [36,37]. Biofilms matrix is a resistance mechanism that could stabilize a bacteria community in a selective environment such as (N)ICUs [38].…”
Section: Resultsmentioning
confidence: 99%
“…En nuestro hospital, sólo se usan CVP de poliuretano que se asocian a menos flebitis que otros materiales 22 , no aplicamos gel antiinflamatorio local y el lumen del catéter es uniforme 20 , de un diámetro no asociado a un mayor riesgo de flebitis 33,34 . Por otra parte, sólo se autorizan conectores sin aguja específicos, descartando aquellos de diseño interior con intrincado, los que se asocian a una alta tasa de bacteriemias [11][12][13][14][15]35 . Este trabajo tiene varias limitaciones que deben ser mencionadas.…”
Section: Discussionunclassified
“…Los conectores sin aguja permitidos requerían la presencia de un tabique interno septado, que no impidiera el flujo laminar y superficies lisas que permitieran una desinfección eficiente y transparentes para la observación de residuo sanguíneo en su interior. Estas características se han asociado a una reducción en el riesgo de complicaciones infecciosas [11][12][13][14][15] .…”
Section: Etapa De Intervenciónunclassified
“…32 From a convenience sample of 62 patients enrolled in the current study, 151 NCs were prospectively obtained for biofilm analysis; biofilm was observed on the luminal surface of >90% of both silvercoated and standard NCs. 33 Microorganisms were recovered by culture from~50% of both NC types, substantially less than those with biofilm burden, but none of the patients from whom these NC cultures were obtained developed a CLABSI. Thus, the relationship between biofilm formation within a NC and subsequent bloodstream infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%